Between Formal Independence and Substantive Empowerment: A Critical Assessment of P3MD Implementation in Kampar Regency, Indonesia - Muammar Alkadafi; Susanti Susanti; Sadu Wasistiono; Mani Festati Broto (Khazanah Sosial, 2025)
This study aims to evaluate the implementation of the Village Development and Empowerment Program (P3MD) in Kampar Regency, Riau, with a particular focus on its effectiveness in realizing the ideal goals of the Independent Village policy. The research is important because, although the number of formally classified independent villages has increased significantly between 2015 and 2024, the substantive achievements of village self-reliance remain questionable. Employing a qualitative multi-case study design, six villages were purposively selected based on the Village Development Index (IDM). Data were collected through interviews, observations, and document analysis, and validated using source triangulation. The findings reveal that P3MD implementation has not been efficient or effective, hindered by overlapping ministerial regulations, central government dominance, sectoral ego between institutions, and policies that lack contextual sensitivity. Additional obstacles include weak community participation, fragile village institutions, and limited administrative as well as human resource capacity. These results imply that a centralized regulatory framework and fragmented institutional arrangements undermine genuine empowerment and delay substantive village transformation. The originality of this study lies in its critical evaluation of the gap between the formal classification of independent villages and their actual capacity for autonomy, offering new insights for policy reform and village governance studies.